ESTIMATES OF CONSUMPTION OF CONFECTIONERY PRODUCTS IN THE AVERAGE DAILY DIETS OF THE POPULATION IN THE WINTER-SPRING SEASON (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
At present, there is no doubt about the principle that nutrition should support physical, mental, and social well-being, contribute to disease prevention, and help improve the health and quality of life of people, including those suffering from various illnesses. Naturally, functional foods are valuable only if they are part of a balanced diet.